PENERAPAN MODEL PEMBELAJARAN BERMAIN PERAN UNTUK MENINGKATKAN KEPERCAYAAN DIRI DAN PRESTASI BELAJAR ILMU PENGETAHUAN SOSIAL (IPS) - Rahman Rahman (DIADIK, 2022)
This study aims to 1) Describe how the application of the learning model plays a role in increasing student self-confidence in social science (IPS) subjects in class V SDN 8 Lahat 2) Describe whether the application of role playing learning models can improve social science learning achievement (IPS). ) students of SDN 8 Lahat 3) Describe how the effectiveness of the application of the learning model plays a role in improving the learning achievement of social science (IPS) students of SDN 8 Lahat. The research design used was classroom action research (PTK) and quasi-experimental. The research subjects were students in class V.A for the PTK class, students in class V.B for the experimental class and students in class V.C for the control class for the even semester of the 2020-2021 school year. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean, percentage, and t-test. The results of the study concluded that the role-playing learning model could increase the self-confidence and social science learning achievement (IPS) of the fifth grade students of SDN 8 Lahat